5x-3y=-6

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 5x from both sides of the equation.

-3y=-6-5x

Divide each term by -3 and simplify.

Divide each term in -3y=-6-5x by -3.

-3y-3=-6-3+-5x-3

Cancel the common factor of -3.

Cancel the common factor.

-3y-3=-6-3+-5x-3

Divide y by 1.

y=-6-3+-5x-3

y=-6-3+-5x-3

Simplify -6-3+-5x-3.

Simplify each term.

Divide -6 by -3.

y=2+-5x-3

Dividing two negative values results in a positive value.

y=2+5×3

y=2+5×3

Reorder 2 and 5×3.

y=5×3+2

y=5×3+2

y=5×3+2

Rewrite in slope-intercept form.

y=53x+2

y=53x+2

Using the slope-intercept form, the y-intercept is 2.

b=2

Find the Y-Intercept 5x-3y=-6